Characterization of the novel HLA‐B*27:198 allele by sequencing‐based typing. (24th June 2020) - Elsermans, Vincent; Visentin, Jonathan; Top, Isabelle; Varlet, Pauline; Labalette, Myriam
Abstract : HLA‐B*27:198 differs from HLA‐B*27:05:02:01 by one nucleotide substitution in codon 45 in exon 2.